Using learning objects technology in learning styles of higher education students / Tan Hock Chuan - Tan, Hock Chuan (2006)
LOOOP (Learning Objects in Object Oriented Programming) is an Electronic Learning (E-Learning) system developed in object-oriented programming based on Learning Objects approach for higher education students. It uses an informational type of Learning Objects technology. The motivation of the project is to provide an alternative system for learners in support learning, provides supportiveness for learners in finding and recording information, provides communication tool for learners as well as to give immediate feedback promptly to learners who need information. This system not only provides user with learning contents, but also provided information searching using the Internet via Google.com. A LOOOP complete system is a client-server application that execute on the client computer and retrieved its learning contents from server or from the client computer itself. This system is developed to support learners who would like to study in a new study style that transformed normal study style into digital environment. To develop fully, linear sequential model had been selected as LOOOP project methodology. Visual Basic was the programming languages used in the project implementation. Besides a client server application, ActiveX control and DLL file was also created in this project for reusability and interoperability purposed. In addition, LOOOP language, which was a similar XML standard language, was used for data passing within database and the system. As a conclusion, a depth defined and designed of LOOOP included its input, output, methodology were required at preliminary stage to ensure LOOOP was developed on the correct path.